2004
DOI: 10.1023/b:joec.0000042065.19044.6d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Long-Range Female Sex Pheromone of the European Tarnished Plant Bug, Lygus rugulipennis: Chemical, Electrophysiological, and Field Studies

Abstract: The European tarnished plant bug, Lygus rugulipennis, is an important pest of agricultural and horticultural crops throughout Europe. Adult male L. rugulipennis were previously shown to be attracted to traps baited with live virgin females, which suggests the females produce a sex pheromone. Volatiles produced by virgin female L. rugulipennis were shown to contain three components, hexyl butyrate, (E)-2-hexenyl butyrate, and (E)-4-oxo-2-hexenal which elicited electroantennographic (EAG) responses from males in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 8 publications
2
61
0
Order By: Relevance
“…For L. rugulipennis, some compounds were identified as components of the sex pheromone (Innocenzi et al 2004), and attraction of males to these compounds has been reported (Innocenzi et al 2005;Fountain et al 2010). However, in traps baited with the two floral attractants discovered in our present study, both sexes of L. rugulipennis were caught, thus these compounds may show practical advantages over the use of sex pheromones.…”
Section: Discussionmentioning
confidence: 96%
“…For L. rugulipennis, some compounds were identified as components of the sex pheromone (Innocenzi et al 2004), and attraction of males to these compounds has been reported (Innocenzi et al 2005;Fountain et al 2010). However, in traps baited with the two floral attractants discovered in our present study, both sexes of L. rugulipennis were caught, thus these compounds may show practical advantages over the use of sex pheromones.…”
Section: Discussionmentioning
confidence: 96%
“…The blend of all three components attracted fewer males than the binary blend (Innocenzi et al, 2005); however, no combination of the three component chemicals was observed to attract males of other species. Innocenzi et al (2004) observed that the release rate of (E)-4-oxohex-2-enal drastically decreased when this compound was in the presence of hexyl butyrate. They considered that this phenomena was caused by the chemical interaction between hexyl butyrate and (E)-4-oxohex-2-enal, so they designated that the butyrates and (E)-4-oxohex-2-enal should be applied separately (Innocenzi et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Although the reason for this inconsistency was not clear, it may have been the influence of the chemical stabilizer and/or sunshade. In the present study, BHT and S-300 were used as chemical stabilizers and an aluminum-foil cup was used as a sunshade, while these were not used by Innocenzi et al (2004Innocenzi et al ( , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three compounds have been identified as components of the ETB female sex pheromone (Innocenzi et al, 2004;Frati et al, 2009) and a blend of these was further optimised and tested in field trials (Innocenzi et al, 2004(Innocenzi et al, , 2005Fountain et al, 2008Fountain et al, , 2011Cross et al, 2011) to develop an effective lure and trap for monitoring males . In addition, some plant volatiles such as phenylacetaldehyde have been identified as attractants for female ETB (Frati et al, 2009;Fountain et al, 2010;Koczor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%